2024
DOI: 10.3390/life14030304
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Anticancer Activity of Natural Methoxylated Flavones Xanthomicrol and Eupatilin in A375 Skin Melanoma Cells

Antonella Rosa,
Franca Piras,
Federica Pollastro
et al.

Abstract: Melanoma is a skin cancer caused by the malignant transformation of melanocytes and cutaneous melanoma represents the most aggressive and deadliest type of skin cancer with an increasing incidence worldwide. The main purpose of the present research was to evaluate the anticancer effects of the natural bioactive compounds xanthomicrol (XAN) and eupatilin (EUP) in human A375 malignant skin melanoma cells, a cell line widely used as an in vitro model of cutaneous melanoma. XAN and EUP are lipophilic methoxylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The canonical SMILES of each identified component were input into the inquiry box of both the STP (retrieved from http://www.swisstargetprediction.ch/, accessed on 5 March 2024) [26] and the SEA database (retrieved from https://sea.bkslab.org/, accessed on 5 March 2024) [70]. Homo sapiens was selected as the species for target prediction.…”
Section: Prediction Of Protein Targets Of Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The canonical SMILES of each identified component were input into the inquiry box of both the STP (retrieved from http://www.swisstargetprediction.ch/, accessed on 5 March 2024) [26] and the SEA database (retrieved from https://sea.bkslab.org/, accessed on 5 March 2024) [70]. Homo sapiens was selected as the species for target prediction.…”
Section: Prediction Of Protein Targets Of Componentsmentioning
confidence: 99%
“…Pharmacological research has shown that it has anti-virus, anti-bacteria, anti-oxidative, anti-inflammatory, anti-dermatitis, gastro-protective, and anti-cancer effects, mainly due to the presence of essential oils, flavonoids, and organic acids [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Pharmacological research has identified various anti-cancer components of Aiye, including jaceosidin, irigenin, luteolin, eriodictyol, apigenin, eupatilin, casticin, and artemetin [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. In obesity, the secretion of adipokines by adipose tissue was dysregulated, characterized by the up-regulation of proinflammation adipokines and the down-regulation of anti-inflammation adipokines [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation